Analisa Kinerja Jaringan Provider Untuk Aplikasi Video Chatting (Studi Kasus Di Daerah Marpoyan) - Jeri Dwi Danur; Febrizal Febrizal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Video chat is a communication that allows users to chat and can see the other person's face directly. Video chatting requires a good network to transmit audio and video data in a short time. This paper examines the performance of three mobile network provider (Provider A and Provider B Provider C) in a video chat in the area Marpoyan and the effect of time when doing video chat on the performance of each provider. The method used is the method using packet sniffing software wireshark to see Quality of Service (QoS) generated by each provider. QoS parameters analyzed such as delay, jitter, packet loss and throughput. Analysis results of data from experiments conducted showed that the best time to do video chat for three provider is at early morning (at 00:00 to 06:00), while the worst time to do video chat on Provider A and Provider B at daytime (12:00 to 18:00) and Provider C at night time (18:00 to 00:00).Keyword: Video chatting, QoS, Packet sniffing